ANALISIS HUBUNGAN TINGKAT KEBISINGAN TERHADAP KELELAHAN KERJA PADA PEKERJA ENGINEERING WORKSHOP DI PT X, JAWA BARAT - Eric Faustine (President University, 2023)
Abstract: Fabrication activities in the factory area have the potential to cause noise. Noise can cause feelings of discomfort, which can lead to difficulties in direct communication, cause cognitive decline, and contribute to job burnout. This study focuses on assessing the noise level caused by activities at the Engineering Workshop PT X, workers' perceptions of work fatigue, and the effect of noise levels on worker fatigue. Objective: This study aims to analyze the noise level, to analyze work fatigue, and to determine the relation of noise level on work fatigue. Method and results: The method used is the measurement of daytime noise levels at the specified point and time and questionnaire data collection. The results of measuring the noise level at the Engineering Workshop PT X, it is known that the lathe area shows a value of 74.1-77.0 dB, the refurbish area shows a value of 84.2-86.9 dB, and the grinding machine area shows a value of 71.5-79.7 dB. Questionnaire data on the level of work fatigue, showed that 25 respondents or 80.6% experienced mild fatigue and 6 respondents or 19.4% experienced moderate fatigue. Chi-Square statistical test showed the value of p = 0.37 (α < 0.05). Conclusion: Only refurbish area that produce noise level above standard. From questionnaire, most of respondents experienced mild fatigue. By using Chi-square analysis, it can be stated that there is no relationship between noise level and work fatigue on workers at Engineering Workshop PT X.